Pure sarcomatous recurrence of clear cell renal carcinoma following radical nephrectomy and dendritic cell vaccination - Antunes, Alberto Azoubel (2006)
CONTEXT: Sarcomatous differentiation, which represents transformation to high-grade malig- nancy, can occur in all histogical types of renal malignancy. CASE REPORT: The authors report on the case of a 66-year-old woman with a right renal mass that was shown to be a clear cell carcinoma. She un- derwent radical nephrectomy and dendritic cell vaccination and, 3.5 years later, she developed retroperitoneal pure sarcomatous recurrence of the tumor. The authors speculate that the vaccination could have played some role in this differentiation or selection of the sarcomatous component of the primary tumor.